2004
DOI: 10.2166/wst.2004.0773
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification with ɛ-caprolactam by acclimated mixed culture and by pure culture of bacteria isolated from polyacrylonitrile fibre manufactured wastewater treatment system

Abstract: The aim of this study is to isolate denitrifying bacteria utilizing epsilon-caprolactam as the substrate, from a polyacrylonitrile fibre manufactured wastewater treatment system. The aim is also to compare the performance of PAN (polyacrylonitrile) mixed bacteria cultures acclimated to epsilon-caprolactam and isolated pure strain for treating different initial epsilon-caprolactam concentrations from synthetic wastewater under anoxic conditions. The result showed that the PAN mixed bacteria cultures acclimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…[9], Rhodococcus equi A4 [10], Rhodococcus erythropolis A10 [11], C. guilliermondii UFMG-Y65 [12], Cryptococcus sp. UFMG-Y28 [13], Brevibacterium imperalis CBS489-74 [14], Rhodococcus rhodochrous LL100-21 [15], Pseudomonas stutzeri [16], Paracoccus thiophilus [17], Kluyveromyces thermotolerans MGBY 37 [18], and Candida guilliermondii CCT 7202 [19]. Microbial biotransformation of nitriles proceeds by two distinct routes; the one-step reaction catalyzed by nitrilase (EC 3.5.5.1) transforms nitriles directly into acids, or the two-step reaction catalyzed by nitrile hydratase (EC 4.2.1.84; NHase) forms amide, which is further hydrolysed to the acid with the release of ammonia by an amidase (EC 3.5.1.4) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[9], Rhodococcus equi A4 [10], Rhodococcus erythropolis A10 [11], C. guilliermondii UFMG-Y65 [12], Cryptococcus sp. UFMG-Y28 [13], Brevibacterium imperalis CBS489-74 [14], Rhodococcus rhodochrous LL100-21 [15], Pseudomonas stutzeri [16], Paracoccus thiophilus [17], Kluyveromyces thermotolerans MGBY 37 [18], and Candida guilliermondii CCT 7202 [19]. Microbial biotransformation of nitriles proceeds by two distinct routes; the one-step reaction catalyzed by nitrilase (EC 3.5.5.1) transforms nitriles directly into acids, or the two-step reaction catalyzed by nitrile hydratase (EC 4.2.1.84; NHase) forms amide, which is further hydrolysed to the acid with the release of ammonia by an amidase (EC 3.5.1.4) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…2). All these bacterial groups have been reported in studies involving solid waste dumpsites [9][10][11][12] except isolate identified as Proteus sp. (strain NTS2).…”
Section: Bacterial Identification and Phylogenetic Analysismentioning
confidence: 99%
“…Optimum temperature for growth experiment The optimum temperature for the growth of the bacterial isolates was determined following the procedure of Lee and Wang (2004) but using 350 mg l À1 of glucose or sodium acetate as the growth substrate under aerobic condition. Optical density at 600 nm was followed as a measurement of growth, and the mid-log growth data for strain was selected for calculating the specific growth rates.…”
Section: -Chlorophenol Degrading Bacteria Identification and Substramentioning
confidence: 99%